Effect of Oil Contamination on the Behavior of Collapsible Soil - Nokande, Saber; Khodabandeh, Mohammad Ali; Besharatinezhad, Ali; Nagy, Gábor; Török, Ákos (Periodica Polytechnica Civil Engineering, 2022)
Loessial soil is moisture-sensitive soil susceptible to settle when fully saturated. In this study, efforts were made to investigate the effect of oil pollutants on mechanical behavior of soil. The loess soil was contaminated by 2,4,6,8 and 10% dry weight of lamp oil and gasoline. Atterberg limits, direct shear, unconfined compressive strength (UCS) and scanning electron microscope (SEM) tests were performed to evaluate the behavior of oil-contaminated collapsible soils. The results of Atterberg tests showed that the plasticity of the soil decreased, due to the reduction in the thickness of the absorbed surface layer and double water layer. According to the direct shear test, with increasing contamination up to 10% of lamp oil and gasoline, the cohesion of the soil was decreased from 14.5 kPa to 7.3 kPa and 7 kPa, respectively, which was due to the reduction in soil plasticity and diffuse double-layer. Because of the lubrication of soil particles, the internal friction angle of soil was reduced from 18.5° to 13.6° and 13.9° for 10% lamp oil and gasoline. UCS of contaminated soil increased in low strains due to the apparent cohesion of hydrocarbons and it decreased 31% for gasoline and 53% for lamp oil at high strains due to the softening behavior of the contaminated soil. SEM test revealed that hydrocarbons covered the soil particles and changed the soil fabrication to dispersed skeleton. Generally, collapsible soil contaminated with different lamp oil and gasoline contents showed a decrease in shear strength and UCS with increasing oil content.